Impacts of high-altitude aerosol hygroscopicity on cloud microphysics in the North China Plain: A WRF fast-SBM modeling study - Qian Gao; Hui He; Xiang'e Liu; Yan Yang; Rong Yuan; Ping Tian; Kai Bi; Fei Wang; Jiujiang Sheng; Yongqing Wang (Atmospheric Research, 2026)

Artemselenolides I–N, sesquiterpenoid trimers from Artemisia selengensis with antihepatoma activity – structural elucidation, molecular docking and dynamics studies - Rong-Kai Chen; Tian-Ze Li; Yong-Cui Wang; Yun-Bao Ma; Ji-Jun Chen (Phytochemistry, 2026)

Shrub encroachment drives multifunctionality trade-offs by reorganizing plant and microbial communities in an alpine meadow - Yang Liu; Hong Xiao; Yuping Rong; Changlin Xu; Ao Han; Kai Ma; Yun Wang (Agriculture, Ecosystems & Environment, 2026)

Synthesis, characterization and application potential of recombinant chicken (Gallus gallus) ferritin with excellent iron-binding capacity and stability - Min Huang; Ranran Pang; Xiaojing Liu; Kai Zhou; Rong Sheng; Yuanyuan Wang; Changyuan Han; Binbin Xu; Han Li; Baocai Xu (Food Bioscience, 2026)

Granite weathering revealed by magnesium isotopes fractionation: Implications for the flux dynamics and global carbon sink - Kai Luo; Jin-Long Ma; Fang-Zhen Teng; Gang-Jian Wei; Guan-Hong Zhu; Jia-Rong Liu; Zhuo-Ying Zhang; Zhi-Bing Wang (Chemical Geology, 2026)

Illumination-induced restructuring of extracellular polymeric substances from Klebsiella Sp. HDJY-1 drives indirect photodegradation of thifensulfuron-methyl - Jiaying Gu; Yaqi Jiao; Chunnan Zhou; Junxin Jia; Siming Li; Kai Wang; Hui Li; Hongtao Shi; Qin Zhou; Rong Liu; Li Li (Water Research, 2026)

Serum exosomes protect heat-stressed mouse 2-cell embryos: Enhanced antioxidant defense and base excision repair of oxidative DNA damage - Hong-Chuan Zhang; Si-Jing Qu; Xin-Lei Yan; Rui-Cong Wang; Shi-Yong Zhu; Rong-Feng Cao; Kai-Qiang Fu; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Statistical and mechanistic analysis of synergetic methanol steam reforming over Ti-based add./Cu-Zn catalysts - Yi-Kai Chih; Shang-Rong Kuo; Jing-Jie Wang; Yi-Xuan Wu (Fuel, 2026)

An approach for detecting hemodynamic parameters in the carotid arterial system based on the priori relationship between blood pressure and arterial radius - Jin Wang; Yong-Jiang Li; Yu-Yuan Zhang; Jing-Rui Gu; Xian-Wei Wang; Dong Chen; Kai-Rong Qin (Medical & Biological Engineering & Computing, 2026)

Differential analysis of lipid profiles in natural Calculus Bovis and Bovis Calculus Sativus by UHPLC-MS/MS - Qiang Mao; Huan Zhong; Wan-Li Liang; Jin Dai; Rui-Ting Huang; Yi-Di Wang; Di-Yang Sun; Kai Tang; Long-Fei Xia; Hai-Biao Gong; Yi-Fang Li; Wan-Yang Sun; et al. (Journal of Natural Medicines, 2026)

Spatiotemporal Patterns, Driving Mechanisms and Responses of Soil Drought to Meteorological Drought in the Yellow River Basin of China - Fei Wang; Wenhan Yu; Yi Zhang; Hexin Lai; Mengting Du; Qian Xu; Rong Li; Ruyi Men; Haoyu Li; Kai Feng; Shikai Gao; Yanbin Li; et al. (International Journal of Climatology, 2026)
With the escalation of global warming, the potential for land evaporation in the Yellow River Basin (YRB) has increased remarkably, and the problem of soil drought has become increasingly prominent. This not only restricts the development of the agricultural economy in the basin, but also intensifies the disparity between water availability and demand, and exerts a profound influence on the ecological security of the basin. In light of this, this study focuses on soil moisture in the YRB from 2000 to 2022, and conducts an in‐depth analysis of the temporal evolution, spatial patterns, abrupt change characteristics as well as the driving forces of soil drought by calculating the Standardised Soil Moisture Index (SSMI). The results show that: (1) Soil drought in the YRB from 2000 to 2022 exhibited a decreasing trend. A negative abrupt change point occurred in February 2004, indicating a sudden intensification of arid conditions. The soil drought in the Above Longyangxia (AL) region exhibited the most significant decreasing trend in September. (2) The most severe soil drought occurred in 2006, and the drought was most intense in November of that year, when the drought‐affected area reaching 86.96%. The severely drought‐stricken areas were predominantly concentrated in the central and northern regions of the basin. (3) The SSMI in the second‐level sub‐regions of the YRB exhibits three types of abrupt changes: increase to decrease, intermittent increase, and decrease to increase, and shows a clear trend from upstream to downstream. (4) The results of cross‐wavelet analysis indicate that soil moisture‐absolute humidity‐soil temperature is the best explanatory combination for soil drought. (5) The slopes of the small‐ and medium‐scale fittings in the AL region are 0.5021 and 0.2584, respectively, and the corresponding mean values of meteorological drought severity are 0.87 and 2.57, respectively. Drought events in the YRB are mainly of medium/short duration and low severity, and soil drought severity tends to increase with the intensification of meteorological drought. This study reveals the spatiotemporal variation patterns of soil drought in the YRB, as well as the responses of climate to soil drought. These findings provide a scientific basis for drought resistance and ecological protection within the basin.

Functional characterization of a canonical C-type lectin from Mytilus coruscus: Roles in innate immunity and feeding processes - Ying-rong Jin; Chuan-yue Chen; Ze-kai Wang; Pan Qin; Zhi Liao; Xiao-lin Zhang; Xiao-jun Yan (Fish & Shellfish Immunology, 2026)

Photoelectron-driven modulation of carbon metabolism enhances hydrogen production in a ZnIn2S4-Shewanella oneidensis biohybrid system - Xue-Meng Wang; Hao-Yu Li; Kai-Li Wang; Zhi-Xuan Zhang; Yu-Xin Cao; Ya-Lian Ma; Rong Chen (Bioresource Technology, 2026)

Corrigendum to “AI-driven process-tolerant BioFET sensing model for precise biliary atresia diagnosis of infants with a single drop of blood” [Chem. Eng. J. (2026), volume 531, 1 March 2026, 173939] - Chia-Kai Lin; Chi-Ming Ku; Chia-Che Wu; Yi-Fang Wu; Huey-Ling Chen; Yueh-Ju Hou; Arnab Pal; Zong-Hong Lin; Chee-Seng Lee; Tzong-Rong Ger; Yu-Lin Wang (Chemical Engineering Journal, 2026)

Recent advances in biochar-based composite phase change materials - Pin Jin Ong; Reuben J. Yeo; Anqi Sng; Suxi Wang; Warintorn Thitsartarn; FuKe Wang; Junhua Kong; Rong Ji; Beng Hoon Tan; Dan Kai; Pei Wang; Jianwei Xu; et al. (Biomass and Bioenergy, 2026)

AI-driven process-tolerant BioFET sensing model for precise biliary atresia diagnosis of infants with a single drop of blood - Chia-Kai Lin; Chi-Ming Ku; Chia-Che Wu; Yi-Fang Wu; Heuy-Ling Chen; Yueh-Ju Hou; Arnab Pal; Zong-Hong Lin; Chee-Seng Lee; Tzong-Rong Ger; Yu-Lin Wang (Chemical Engineering Journal, 2026)

Metabolic engineering of Pichia pastoris for high-efficiency production of branched-chain amino acids -enriched single-cell protein - Cancan Dong; Kai Hong; Fan Wu; Yanfeng Wang; Youyan Rong; Xin Wu; Jian Zhang; Le Gao (Bioresource Technology, 2026)

Soil Fungi Composition and Functional Groups in Phosphate Mine Spontaneous Recovery Areas: A Combined High‐Throughput and Traditional Approaches - Yongsheng Peng; ChengJiao Dao; YuRong Wang; Rong Tang; Neelamanie Yapa; Garumuni Dilrukshi Nadeeshani Menike; Anuruddha Karunarathna; Abdallah M. Elgorban; Alanoud T. Alfagham; Saowaluck Tibpromma; Y. A. P. K. Dayasena; Kai Yan (New Zealand Journal of Botany, 2026)
Our study on the composition and functional groups of soil fungi in phosphate mine spontaneous recovery areas has identified several fungal genera that play a crucial role in soil regeneration. This finding carries significant practical implications for the methodologies employed in mine site reclamation. We used amplicon sequencing‐based high‐throughput sequencing (HTS) and traditional fungal culturing methods in the Kunyang phosphate mining area of Kunming City, Yunnan Province, China, to comprehensively assess fungal community composition and functional diversity during spontaneous regeneration. The fungal communities in the natural recovery area differ significantly from those in the abandoned mining area, exhibiting notably higher fungal diversity indices and a more complex co‐occurrence pattern. Through HTS, 13 fungal phyla and 447 fungal genera were identified. Among them, Ascomycota is the dominant phylum, followed by Basidiomycota , and Mortierella was the primary genus. All cultured fungi belong to Ascomycota , comprising 16 genera, among which Purpureocillium and Penicillium are predominant. The majority of cultured fungi belong to pathogenic and saprophytic groups, while Mortierella is the only potential symbiotic genus. Notably, six fungal genera were identified exclusively through culturable approaches: Aureobasidium , Cladosporium , Cytospora , Discohainesia , Neopyrenochaeta , and Saccharomyces . These genera play a crucial role in soil regeneration, and their identification is a significant step toward understanding their functional characteristics. The results indicate that rhizosphere fungal communities vary significantly under distinct restoration strategies. This underscores the importance of considering regional specificity, such as local climate and soil conditions, when harnessing fungi for vegetation rehabilitation. The synergistic application of high‐throughput sequencing alongside culturable methods is not only beneficial but also crucial for the efficient screening and utilization of functional fungi. This integration reassures professionals in the field about the effectiveness and reliability of their research methods, thereby enhancing their confidence in the outcomes.

Development of polydopamine/Cobalt single atom co-doped Al2O3 ceramic membrane: An effective strategy for oil-wastewater treatment - Junjie Wang; Kai Wang; Yuanfeng Chen; Yu Xue; Xinlei Wang; Weiguang Lan; Shengqiong Fang; Rong Fan (Environmental Research, 2026)

Evolution of tactoid structures and pore water distribution during wetting in saturated clay aggregates driven by montmorillonite-water interaction - Kai-wen Tong; Chang-fu Wei; Yong-gui Chen; Zi-yu Ding; Hao Wang; Ya-kun Tian; Rong Gui; Ling-ling Wu; Zhi-jun Zhang; Lin Hu (Computers and Geotechnics, 2026)

Efficient production of medium-chain fatty acids in engineered Escherichia coli strains from ionic liquids pretreated bamboo enzymatic hydrolysate with carbon dioxide fixation - Ling Zhou; Kun Rong; Kai-Xing Xiao; Ruo-Shi Luo; Zhao Qin; Rustam Iqra; Xia Fang; Jikai Zong; Zhiyao Peng; Min Long; Dan Wang (Bioresource Technology, 2026)

CRODNet: Cascaded learning network for contactless top-view cattle rotated object detection - Hui Kang; Yuqi Zhang; Longxiang Li; Chunyang Li; Sen Wang; Kai Niu; Yue Rong; Zhiqiang He (Computers and Electronics in Agriculture, 2026)

Arthroderma guizhouense sp. nov., a Novel Geophilic Species from Guizhou, China - Kai-Rong Wang; Heng Pan; Bing-Da Sun; Gang Tao; Zhi-Yuan Zhang (Mycopathologia, 2025)

Limonoids and protolimonoid from Swietenia macrophylla - Yun-Peng Sun; Wen-Fang Jin; Ze-Rong Xu; Ying-Wei Liu; Li-Juan Sun; Yang Yu; Jin-Song Liu; Guo-Kai Wang (Natural Product Research, 2025)

Multifunctional integrated separator based on electrospinning structure engineering for high-stability lithium sulfur batteries - Chaojiang Fan; Rong Yang; Bing Chen; Qing Huang; Lingjiang Kou; Jiajia Song; Yong Wang; Teng Wang; Yinglin Yan; Zhongguo Zhao; Kai Jia; Wenhu Li; et al. (Chemical Engineering Journal, 2025)

Residual polyacrylamide-induced membrane fouling in short-flow coagulation-ultrafiltration: Behavior and mechanism - Mohan Wei; Yaozhong Zhang; Xing Zheng; Chi Zhang; Jiheng Duan; Kai Guo; Menghan Wang; Dongfei Li; Tianshuo Huang; Rong Chen (Chemical Engineering Journal, 2025)

Formation of the giant Jinduicheng porphyry Mo deposit in East Qinling, Central China: Evidence from geochemical and isotopic compositions of magmatic accessory minerals - Kai Xing; Qihai Shu; David Lentz; Rong Xu; Fangfang Zhang; Jinyu Liu; Fan Yu; Xudong Niu; Qingfei Wang; Jun Deng (Lithos, 2025)

Synergistic antimicrobial effect and mechanism of enterocin Gr17 and cinnamaldehyde against Escherichia coli and Candida albicans - Wen-yu Ma; Kai-sheng Shen; Zhao Wang; Qi Liu; Xin-jie Diao; Guo-rong Liu (Archives of Microbiology, 2025)

Application of biochar in saline soils enhances soil resilience and reduces greenhouse gas emissions in arid irrigation areas - Shixiong Ren; Jiawang Zhong; Kai Wang; Rong Liu; Hao Feng; Qin’ge Dong; Yuchen Yang (Soil and Tillage Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Elimination of antibiotic resistance genes and adaptive response of Firmicutes during chicken manure composting - Wei-Li Jia; Ben Wang; Lu-Kai Qiao; Fang-Zhou Gao; Wang-Rong Liu; Liang-Ying He; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Exploring morphological heterogeneity of circulating tumor cells: machine learning-based approach for cell identification and prognostic implications - Peng-Xiang Wang; Yu-Chen Zhong; Bin Duan; Jian-Wen Cheng; Yun-Fan Sun; Wen-Jing Zheng; Kai-Qian Zhou; Yang Xu; Hai-Xiang Peng; Wei-Xiang Jin; Hai-Min Li; Xiao-Juan Sun; et al. (Science Bulletin, 2025)

Analysis of CO2 emission and energy consumption in CCUS for steel-chemical joint production - Huapeng Yang; Chao Feng; Tao Lin; Rong Zhu; Kai Dong; Guangsheng Wei; Mingwei Tu; Fuhai Liu; Ziheng Zhao; Xin Ren; Chunyang Wang (Journal of Environmental Management, 2025)

Independent and joint effects of volatile organic compounds on pulmonary function in U.S. adults from NHANES: the mediating role of platelet-to-lymphocyte ratio - Yan-Fei Wei; Hao-Wen Chen; Kuan Liu; Shi-Ao Wang; Wei-Dong Fan; Zhan-Hui Shao; Bi-Fei Cao; Yong-Qi Liang; Zheng-Yun Xu; Kai-Yue Liao; Zi-Xuan Zhao; Lu-Rong Yang; et al. (Environmental Pollution, 2025)

Machine learning-driven molecular generation for accelerated screening of high-performance flame retardants in epoxy resin composites - Zhongwei Chen; Chunlei He; Kai Wang; Feng Rong; Long Xiang; Ziwei Zuo; Changliang Wang; Xinyuan Yang; Yong Guo; Juncheng Jiang; Yuan Yu (Chemical Engineering Journal, 2025)

Progressive collapse resistance of prestressed precast concrete substructures with slot-bolted top-seat angles - Hai-Rong Shi; Bin Zeng; Kai Qian; Chun-Lin Wang (Engineering Structures, 2025)

Predicting the blast-induced ground vibration with support vector regression optimized by five swarm algorithms - Kai Rong; Xuan Xu; Haibo Wang; Jun Yang (Earth Science Informatics, 2025)

Ultrafast self-gelling, superabsorbent, and adhesive chitosan-based hemostatic powders for rapid hemostasis and wound healing - Ashuang Liu; Shengyong Cui; Lei Song; Xiangshu Guo; Zhimao Huang; Shancan Wang; Kai Cheng; Ying Xiao; Youfen Fan; Rong Wang (Carbohydrate Polymers, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Environmental determinants of spatial-temporal variability in ammonia oxidizing microorganisms across diverse Chinese agricultural soils - Aiju Liu; Fangxu Rong; Guizhen Wang; Guoqin Hou; Jing Liu; Mingyue Li; Kai Liu; Zafran Gul Wazir; Hongliang Liu; Yuzhi Xu (Journal of Environmental Management, 2025)

Precipitation changes reshape desert soil microbial community assembly and potential functions - Kai Sun; Rong Yang; Jiliang Liu; Wenzhi Zhao; Xiaojun Li; Yongzhen Wang; Shujun Song (Environmental Research, 2025)

Numerical evaluation on spray cooling to mitigate heat stress in cattle using computational fluid dynamics - Ruimin Yang; Wenqi Zhang; Christopher Y. Choi; Li Rong; Guoqiang Zhang; Kai Liu; Xiaoshuai Wang (Computers and Electronics in Agriculture, 2025)

Highly active Cu-embedded in magnetic carbon nanofibers for the reduction of 4-nitrophenol - Ching-Shiun Chen; Tse-Ching Chen; Kai-Lin Chiu; Cheng-Rong Hsing; Li-Yu Wang; Chia-Min Yang; Chih-Wen Pao; Chi-Liang Chen (Chemical Engineering Journal, 2025)

Weavable composite filament for sustained electricity generation from multiple sources - Rong Liu; Haoyu Li; Zhenzhou Fu; Hailou Wang; Jiamu Dai; Kai Dong; Ick Soo Kim; Wei Zhang (Chemical Engineering Journal, 2025)

The correlation between single and mixed trace elements exposure in systemic lupus erythematosus: A case-control study - Rong-Gui Huang; Kai-Di Li; Hong Wu; Yi-Yu Wang; Ya Xu; Xue Jin; Yu-Jie Du; Yi-Yuan Wang; Jing Wang; Zhang-Wei Lu; Bao-Zhu Li (Journal of Trace Elements in Medicine and Biology, 2024)

Engineered multienzyme-mimicking 2D bismuthene catalytic nanotriggers enable cascade enzyodynamic-boosted and synergistic GPX4/FSP1-mediated ferroptosis amplification for cancer radiosensitization - Yipengchen Yin; Li Zhu; Tiaoyan Jiang; Rong Chai; Ya Zhang; Tianyu Li; Kai Wang; Sheng Wang; Qin Zhang (Chemical Engineering Journal, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Dual isotope analysis reveals the COVID-19 lockdown impact on nitrate aerosol sources and formation pathways in Shanghai - Rong Wang; Hao Xiao; Yu Xu; Ai-Min Long; Min Zhou; Wen-Kai Guan; Hua-Yun Xiao; Hong-Wei Xiao (Science of The Total Environment, 2024)

Metagenomic analysis unveiled the response of microbial community and antimicrobial resistome in natural water body to duck farm sewage - Chang Fang; Kai-di Liu; Feng-jie Tian; Jin-ying Li; Si-jie Li; Rong-min Zhang; Jian Sun; Liang-xing Fang; Hao Ren; Min-ge Wang; Xiao-ping Liao (Environmental Pollution, 2024)

Polymerizable deep eutectic solvent enables flexible gel formation for motion sensor and anti-UV film - Shanlei Chang; Kai Rong; Yuchen Wang; Zhixuan Yu; Junfeng Zhai; Hongwei Tian; Youxing Fang; Shaojun Dong (Chemical Engineering Journal, 2024)

Gene expression profiles and metabolic pathways responsible for male sterility in cybrid pummelo - Rong Wang; Yang-Cao Shi; Bo Zhang; Wan-Rong Liu; Feng-Quan Tan; Fang Lu; Nan Jiang; Lai-Chao Cheng; Kai-Dong Xie; Xiao-Meng Wu; Wen-Wu Guo (Plant Cell Reports, 2024)

Development of an efficient pretreatment process and multi-functional acetate co-metabolism strategy for the treatment of high strength biogas slurry using a newly isolated Chlorella sorokiniana - Ning Jiao; Xiao Cheng; Yuan Sun; Yu-Rong Zhu; Zhong-Liang Sun; Shi-Kai Wang (Chemical Engineering Journal, 2024)

Metabolic Heterogeneity and Potential Immunotherapeutic Responses Revealed by Single-Cell Transcriptomics of Breast Cancer - Shicong Tang; Qing Wang; Ke Sun; Ying Song; Rui Liu; Xin Tan; Huimeng Li; Yafeng Lv; Fuying Yang; Jiawen Zhao; Sijia Li; Pingping Bi; et al. (Apoptosis, 2024)

MicroRNA dynamics in irisin-mediated signaling pathways within adipose tissue - Ming-Yun Ho; Kai-Pin Chiu; Ming-Lung Tsai; Jih-Kai Yeh; Yi-Chun Huang; Yan-Rong Li; Horng-Dar Wang; I-Chang Hsieh; Ming-Shien Wen; Chao-Yung Wang (Journal of Biosciences, 2024)

Remediation of Composite Contaminated Soil by Lead, Arsenic, Uranium and Thorium of Radioactive and Heavy Metal Using Chemical Drenching Combined with Passivation - Linxi Zhang; Jingwen Wang; Rong Zou; Dongxiang Xie; LiangLiang Chen; Honghai Wang; Kai Zeng; Ying Dai (Water, Air, & Soil Pollution, 2024)

The response of Martian photoelectron boundary to the 2018 global dust storm - Yuqi Wang; Jun Cui; Yong Wei; Zhaopeng Wu; Kai Fan; Zhaojin Rong; Fei He; Yutian Cao; Jiawei Gao (Science China Earth Sciences, 2024)

Argon non-thermal plasma treatment promotes the development of rice (Oryza sativa L.) in saline alkali environments - Kai Liu; Yan-Jiang Feng; Jun-Xiang Guo; Gui-Ling Wang; Li-Li Shan; Shi-Wei Gao; Qing Liu; Hu-Nan Sun; Xi-Yu Li; Xing-Rong Sun; Jing-Yang Bian; Taeho Kwon (Protoplasma, 2024)

Prediction of the mean fragment size in mine blasting operations by deep learning and grey wolf optimization algorithm - Kai Rong; Xuan Xu; Haibo Wang; Jun Yang (Earth Science Informatics, 2024)

Chemical constituents of the deep-sea-derived fungus Trichoderma simmonsii ZEN3 and their chemotaxonomic significance - Li-Fang Liu; Yuan Wang; Rong Chao; Lin Xu; Zheng-Biao Zou; Kai Zhang; Ming-Min Xie; Xian-Qiang Chen; Cheng-Hai Gao; Xian-Wen Yang (Biochemical Systematics and Ecology, 2024)

Overview of the recent advances in porcine epidemic diarrhea vaccines - Miao-Zhan Wei; Lan Chen; Rong Zhang; Ze Chen; Yan-Juan Shen; Bi-Jun Zhou; Kai-Gong Wang; Chun-Lan Shan; Er-Peng Zhu; Zhen-Tao Cheng (The Veterinary Journal, 2024)

Use of machine learning to identify key factors regulating volatilization of semi-volatile organic chemicals from soil to air - Rong Wang; Kai-Hui Zhang; Yu Wang; Chen-Chou Wu; Lian-Jun Bao; Eddy Y. Zeng (Science of The Total Environment, 2024)

The double-edged effects of La2O3 and CeO2 on the performance of high-rate anaerobic sludge bed reactors and microbial mechanisms - Kai Su; Lin-xiao Li; Zhuo Zeng; Xue Yang; Tao Lei; Han Zhang; Qin Wang; Rong Cao (Process Safety and Environmental Protection, 2024)

Comparative analysis of process selection and carbon emissions assessment of innovative steelmaking routes - Botao Xue; Guangsheng Wei; Yanze Hou; Hang Hu; HongJin Zhang; Rong Zhu; Kai Dong; Chao Feng; Lingzhi Yang; Hongbin Wang (Journal of Cleaner Production, 2024)

A pair of new chromone enantiomers from Xylaria nigripes - Jing Li; Yue-Ping Jiang; Lan-Qing Li; Hong-Ping Long; Hai-Tao Liu; Rong Yang; Shao Liu; Wen-Xuan Wang; Ji-Kai Liu (Natural Product Research, 2024)

Screening of small molecule compounds targeting hnRNPA2 protein - Yuan-Rong Zheng; Chao-Jie Wang; Ling Yang; Yu-Jun Zhang; Mei-Juan Fang; He Chang; Kai-Qiang Guo; Song-Lin Shi (Medicinal Chemistry Research, 2023)

Urine 2-hydroxyphenanthrene is associated with current asthma: evidence from NHANES 2007–2012 - Lingyi Lu; Tingfeng Mao; Rui Xu; Lanxia Liu; Jiefeng Qian; Kai Yang; Anjie Yuan; Xinyue Wang; Rong Ni (International Archives of Occupational and Environmental Health, 2023)

Which molecular marker is better? Comparative analyses of COI and ITS2 in molecular identification of Trichogramma (Hymenoptera: Trichogrammatidae) - Ao-Kai Wang; Fang-Yi Li; De-Sen Wang; Yu-Rong He; Yuan-Xi Li; Zhi-Chao Yan (BioControl, 2023)

The occurrence of "yellowing" phenomenon and its main driving factors after the remediation of chromium (Cr)-contaminated soils: A literature review - Hao-Kai Li; Da-Mao Xu; Jun-Xian Wang; Ze-Lin Xu; Rong-Bing Fu (Journal of Hazardous Materials, 2023)

Mechanism of arsenic distribution and migration during iron extraction by copper slag-steel slag combined reforming: A potential solution to refractory wastes - Yun Zhou; Hongyang Wang; Haichuan Wang; Kai Dong; Rong Zhu; Zhenqiang Jiang; Guangsheng Wei (Journal of Cleaner Production, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Endocrine-disrupting chemicals and autoimmune diseases - Rong-Gui Huang; Xian-Bao Li; Yi-Yu Wang; Hong Wu; Kai-Di Li; Xue Jin; Yu-Jie Du; Hua Wang; Fang-Yi Qian; Bao-Zhu Li (Environmental Research, 2023)

Applicability of carbonate clumped isotope thermometry in the Tuchang-Jentse geothermal field - Yi-Chia Lu; Sheng-Rong Song; Ling-Wen Liu; Tsung-Ren Peng; Bill Bing-Cheng Chen; Remy Kai-Cheng Tu; Li-Hung Lin; Pei-Ling Wang (Geothermics, 2023)

The city-wide full-scale interactive application of sewage surveillance programme for assisting real-time COVID-19 pandemic control – A case study in Hong Kong - Wai-yin Ng; Wai Thoe; Rong Yang; Wai-ping Cheung; Che-kong Chen; King-ho To; Kan-ming Pak; Hon-wan Leung; Wai-kwan Lai; Tsz-kin Wong; Tat-kwong Lau; Ka-wing Au; et al. (Science of The Total Environment, 2023)

Far-field Coupling and Interactions in Multiple Geospheres After the Tonga Volcano Eruptions - Chieh-Hung Chen; Yang-Yi Sun; Xuemin Zhang; Fei Wang; Kai Lin; Yongxin Gao; Chi-Chia Tang; Jun Lyu; Rong Huang; Qian Huang (Surveys in Geophysics, 2023)

Chinese version of the auditory verbal learning test: normative study and clinical applications in Chinese-speaking population in Shijiazhuang city - Fang-Ming Dong; Wei Wang; Shang-Zun Guo; Kai Shao; Ya-Xue Song; Ning Han; Yan-Li Jia; Rong-Fang Feng; Jian-Hua Wang (Acta Neurologica Belgica, 2023)

Responses of Bacillus sp. under Cu(II) stress in relation to extracellular polymeric substances and functional gene expression level - Ling-ling Wang; Zheng-yan Yin; Yun Xu; Miao-yu Deng; Kai-ming Zhang; Quan Wang; Rong-ping Chen; Lei Yu (Environmental Science and Pollution Research, 2023)

Essential Trace Element Status in Systemic Lupus Erythematosus: a Meta-analysis Based on Case-Control Studies - Hua Wang; Xian-Bao Li; Rong-Gui Huang; Nv-Wei Cao; Hong Wu; Kai-Di Li; Yi-Yu Wang; Bao-Zhu Li (Biological Trace Element Research, 2023)

Exploring the impact of emissions trading schemes on income inequality between urban and rural areas - Kai Fang; Mengyuan Mao; Chuanhao Tian; Jing Chen; Wenjing Wang; Rong Tan (Journal of Environmental Management, 2023)

Estimating divergent forest carbon stocks and sinks via a knife set approach - Shitephen Wang; Keito Kobayashi; Satoru Takanashi; Chiung-Pin Liu; Dian-Rong Li; San-Wen Chen; Yu-Ting Cheng; Kai Moriguchi; Masako Dannoura (Journal of Environmental Management, 2023)

Constructing redox-active 3D covalent organic frameworks with high-affinity hexameric binding sites for enhanced uranium capture - Yi-Ru Chen; Xiu Wang; Wei Xu; Kai Liu; Wei-Bin Qiu; Yongquan Wu; Yibao Li; Wei-Rong Cui (Chemical Engineering Journal, 2023)

Rapid, linear, and highly reliable structural-color switching enabled by thermal regulation of chiral nematic mesophases - Dong Li; Rong-Rong Jiang; Si-Kai Chen; Jia-Min Wu; Xiu Dong; Xiu-Li Wang; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2023)

A new acylated iridoid and other chemical constituents from Valeriana jatamansi and their biological activities - Yun Wang; Dao-Qun Shi; Na Jiang; Kai-Rui Rao; Shi-Xian Zhang; Dan Liu; Rong-Tao Li; Hong-Mei Li (Natural Product Research, 2023)

Dose–response mapping of MEHP exposure with metabolic changes of trophoblast cell and determination of sensitive markers - Yiwei Fang; Zhiliang Chen; Jinyu Chen; Minqi Zhou; Yuanyao Chen; Rong Cao; Chunyan Liu; Kai Zhao; Min Wang; Huiping Zhang (Science of The Total Environment, 2023)

Effects of substituting municipal waste incineration fly ash for lime on generating a bonding phase during the sintering process - Zhenqiang Jiang; Kai Dong; Hongyang Wang; Yun Zhou; Bohan Tian; Xin Li; Rong Zhu (Journal of Cleaner Production, 2023)

Combining a novel biofilm reactor with a constructed wetland for rural, decentralized wastewater treatment - Rui Zhang; Xianchang Liu; Lutian Wang; Pan Xu; Kai Li; Xiaoxiao Chen; Rong Meng; Yuewu Pu; Xuetong Yang; Diederik P.L. Rousseau; Stijn W.H. Van Hulle (Chemical Engineering Journal, 2023)

Proteomic analysis and identification reveal the anti-inflammatory mechanism of clofazimine on lipopolysaccharide-induced acute lung injury in mice - Bo Yang; Zhan Gao; Qi-Shuang Li; Xiang-Ye Zhang; Lan Song; Yi-Ni Wang; Xin-Yue Wang; Lin-Lin Ji; Hong-Liang Xu; Hui Xie; Fu-Kai Feng; Xiao-Ping Li; et al. (Inflammation Research, 2022)

Identification of resistance of Guangxi (Oryza rufipogon Griff.) to white-backed planthopper with stem evaluation method - Xin-ying Guo; Xuan Wang; Liang Luo; Yao-yu Fang; Kai-chong Teng; Neng Zhao; Jin-lian Yang; Fang Liu; Bao-xiang Qin; Ji-jing Luo; Rong-bai Li (Genetic Resources and Crop Evolution, 2022)

Sugar Product Diversification and Its Opportunities in China - Qi Wang; Cai-Feng Xie; Chang-Rong Shi; Yuan Li; Yu-Hao Shang; Chu-Xuan Hou; Fang-Xue Hang; Jian-Bin Li; Kai Li (Sugar Tech, 2022)

The solar wind plasma upstream of Mars observed by Tianwen-1: Comparison with Mars Express and MAVEN - Kai Fan; Limei Yan; Yong Wei; Aibing Zhang; Linggao Kong; Markus Fränz; Fei He; Lihui Chai; Chongjing Yuan; Yuqi Wang; Jun Zhong; Zhaojin Rong; et al. (Science China Earth Sciences, 2022)

Caffeine Inhibits Activation of the NLRP3 Inflammasome via Autophagy to Attenuate Microglia-Mediated Neuroinflammation in Experimental Autoimmune Encephalomyelitis - Hui-Qi Wang; Kai-Yi Song; Jin-Zhou Feng; Si-Yuan Huang; Xiu-Ming Guo; Lei Zhang; Gang Zhang; Ying-Chao Huo; Rong-Rong Zhang; Yue Ma; Qing-Zhe Hu; Xin-Yue Qin (Journal of Molecular Neuroscience, 2022)

Wisdom, predicaments, and challenges of a millennium ancient weir—Dujiangyan Project - Xiao-rong Huang; Xing-yu Zhou; Jin-jun You; Qing Yang; Yan-jun Wang; Kai Ma (Journal of Mountain Science, 2021)

Phenomic and metabolomic responses of roots to cadmium reveal contrasting resistance strategies in two rice cultivars (Oryza sativa L.) - Chong Liu; Mo-ming Lan; Er-kai He; Ai-jun Yao; Guo-bao Wang; Ye-tao Tang; Rong-liang Qiu (Soil Ecology Letters, 2021)

Transcutaneous Auricular Vagus Nerve Stimulation: From Concept to Application - Yu Wang; Shao-Yuan Li; Dan Wang; Mo-Zheng Wu; Jia-Kai He; Jin-Ling Zhang; Bin Zhao; Li-Wei Hou; Jun-Ying Wang; Lei Wang; Yi-Fei Wang; Yue Zhang; et al. (Neuroscience Bulletin, 2021)

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

Small RNA Sequencing Analysis of Germinating Single-bud Seedcane Sett in Sugarcane - Kai-Chao Wu; Lin Xu; Zhi-Nian Deng; Tian Pang; Rong-Hua Zhang; Yi-Jie Li; Xiao-Yan Liu; Cheng-Feng Huang; Wen-Xian Qin; Jian-Feng Wei; Li-Ping Wei; Yang-Rui Li; et al. (Sugar Tech, 2021)

Cathepsin V Mediates the Tazarotene-induced Gene 1-induced Reduction in Invasion in Colorectal Cancer Cells - Chun-Hua Wang; Lu-Kai Wang; Chang-Chieh Wu; Mao-Liang Chen; Chan-Yen Kuo; Rong-Yaun Shyu; Fu-Ming Tsai (Cell Biochemistry and Biophysics, 2020)

Predictors of nasal bacterial culture rates in patients with chronic rhinosinusitis - Jing-Jie Wang; Chih-Yi Chen; Kai-Li Liang; Rong-San Jiang (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Functional Analysis of Sheep POU2F3 Isoforms - Guang-Wei Ma; Yan-Kai Chu; Hua Yang; Xiao-Hong Yan; En-Guang Rong; Hui Li; Ning Wang (Biochemical Genetics, 2020)
POU domain class 2 transcription factor 3 (POU2F3) plays an important role in keratinocyte proliferation and differentiation. Our previous study identified four sheep POU2F3 transcript variants ( POU2F3-1 , POU2F3-2 , POU2F3-3 , and POU2F3-4 ), encoding three POU2F3 protein isoforms (POU2F3-1, POU2F3-2, and POU2F3-3). However, the functional differences among the three POU2F3 isoforms remain unknown. The objective of this study was to determine the tissue expression pattern of the four POU2F3 transcript variants in sheep and to investigate the functional differences in cell proliferation among the three POU2F3 isoforms. Quantitative RT-PCR analysis showed that the four POU2F3 transcripts were ubiquitously expressed in all tested adult sheep tissues, and POU2F3-1 exhibited higher expression level than the other three POU2F3 transcript variants in skin ( P P P P > 0.05). Dual luciferase reporter assays demonstrated that overexpression of any one of the three POU2F3 isoforms significantly inhibited the promoter activities of keratin 14 ( KRT14 ) and matrix metalloproteinase 19 ( MMP19 ) genes ( P KRT14 and MMP19 genes than POU2F3-1 and POU2F3-2 ( P P > 0.05). These results suggest three sheep POU2F3 isoforms have similar functional effects, but to a different extent.

First report of isolation and complete genome of Vibrio rotiferianus strain SSVR1601 from cage‐cultured black rockfish ( Sebastes schlegelii ) associated with skin ulcer - Zheng Zhang; Yong‐xiang Yu; Yong Jiang; Yin‐geng Wang; Mei‐jie Liao; Xiao‐jun Rong; Kai Wang; Hao Zhang; Jing Chen (Journal of Fish Diseases, 2019)
Vibrio rotiferianus is an important marine pathogen of various aquatic organisms and can be found widely distributed in the marine environment. To further characterize this pathogen, the pathogenic properties and genome of V. rotiferianus SSVR1601 isolated from Sebastes schlegelii with skin ulcer were analysed. SSVR1601 was shown to be short rod‐shaped cell with a single polar flagellum. Different degrees of pathological changes in fish kidney, intestine, gills and liver were observed after SSVR1601 challenge. The SSVR1601 genome consists of two chromosomes and two plasmids with a total of 5,717,113 bp, 42.04%–44.93% GC content, 5,269 predicted CDSs, 134 tRNAs and 40 rRNAs. The common virulence factors including OMPs, haemolysin, flagellin, DNase, entF , algU , tcpI , acfB and rfaD were found in strain SSVR1601. Furthermore, factors responsible for iron uptake ( fur , fepC and ccmC ) and types II, IV and VI secretion systems were detected, which are likely responsible for the pathogenicity of SSVR1601. The antimicrobial resistance genes, bacA , tet34 and norM, were detected based on Antibiotic Resistance Genes Database. The phylogenetic analysis revealed SSVR1601 to be most closely related to V. rotiferianus strains CAIM577 and B64D1.

Effects of the arterial radius and the center-line velocity on the conductivity and electrical impedance of pulsatile flow in the human common carotid artery - Hua Shen; Siqi Li; Yu Wang; Kai-Rong Qin (Medical & Biological Engineering & Computing, 2019)

Cretaceous A-type volcanic–intrusive rocks and simultaneous mafic rocks along the Gan-Hang Tectonic Belt, Southeast China: petrogenesis and implications for the transition of crust–mantle interaction - Hong-Zuo Wang; Pei-Rong Chen; Kai-Xing Wang; Hong-Fei Ling; Jun-Qi Wu; Jiang-Wei Tang; You-Dong Zhao (International Geology Review, 2018)

Co-targeting PLK1 and mTOR induces synergistic inhibitory effects against esophageal squamous cell carcinoma - Ting-Ting Liu; Kai-Xia Yang; Jing Yu; Ying-Ya Cao; Jian-Song Ren; Jia-Jie Hao; Bei-Qing Pan; Sai Ma; Li-Yan Yang; Yan Cai; Ming-Rong Wang; Yu Zhang (Journal of Molecular Medicine, 2018)

Knockdown expression of IL-10Rα gene inhibits PRRSV replication and elevates immune responses in PBMCs of Tibetan pig in vitro - Yihui Chen; Ye Wang; Kai Zeng; Yun-feng Lei; Xiao-hui Chen; San-cheng Ying; Xue-Bin Lv; Zezhou Wang; Rong Gao (Veterinary Research Communications, 2018)

Genetic mapping of the qGCR6 locus affecting glossiness of cooked rice - Sheng-Shan Wang; Kai-Yi Chen; Yann-Rong Lin; Rong-Kuen Chen (Euphytica, 2017)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Molecular identification and expression of the Foxl2 gene during gonadal sex differentiation in northern snakehead Channa argus - Dan-Dan Wang; Gui-Rong Zhang; Kai-Jian Wei; Wei Ji; Jonathan P. A. Gardner; Rui-Bin Yang; Kun-Ci Chen (Fish Physiology and Biochemistry, 2015)

Ecotoxicity of two organophosphate pesticides chlorpyrifos and dichlorvos on non-targeting cyanobacteria Microcystis wesenbergii - Kai-Feng Sun; Xiang-Rong Xu; Shun-Shan Duan; You-Shao Wang; Hao Cheng; Zai-Wang Zhang; Guang-Jie Zhou; Yi-Guo Hong (Ecotoxicology, 2015)

Spiculisporic acid analogues of the marine-derived fungus, Aspergillus candidus strain HDf2, and their antibacterial activity - Rong Wang; Zhi Kai Guo; Xiang Min Li; Fu Xiao Chen; Xia Fei Zhan; Ming Hui Shen (Antonie van Leeuwenhoek, 2015)

Rapid detection of copper chlorophyll in vegetable oils based on surface-enhanced Raman spectroscopy - Wei-Nan Lian; Jessie Shiue; Huai-Hsien Wang; Wei-Chen Hong; Po-Han Shih; Chao-Kai Hsu; Ching-Yi Huang; Cheng-Rong Hsing; Ching-Ming Wei; Juen-Kai Wang; Yuh-Lin Wang (Food Additives & Contaminants: Part A, 2015)

ZSTK474, a novel PI3K inhibitor, modulates human CD14+ monocyte-derived dendritic cell functions and suppresses experimental autoimmune encephalomyelitis - Zhenyi Xue; Wen Li; Huafeng Wang; Biao Huang; Zhenzhen Ge; Chao Gu; Ying Liu; Kai Zhang; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; et al. (Journal of Molecular Medicine, 2014)

Fasudil Hydrochloride Protects Neurons in Rat Hippocampal CA1 Region through Inhibiting GluR6–MLK3–JNKs Signal Pathway - Xiu-E Wei; Feng-Yu Zhang; Kai Wang; Qing-Xiu Zhang; Liang-Qun Rong (Cell Biochemistry and Biophysics, 2014)

Large-scale screening maize germplasm for low-phosphorus tolerance using multiple selection criteria - Li-tian Zhang; Jia Li; Ting-zhao Rong; Shi-bin Gao; Feng-kai Wu; Jie Xu; Meng-lu Li; Mo-ju Cao; Jing Wang; Er-liang Hu; Ya-xi Liu; Yan-li Lu (Euphytica, 2014)

Isolation and characterization of twenty-three polymorphic microsatellite loci in Schizothorax macropogon - Xiang-Zhao Guo; Gui-Rong Zhang; Ruo-Jin Yan; Wei Ji; Rui-Bin Yang; Kai-Jian Wei; Deng-Qiang Wang (Conservation Genetics Resources, 2014)

Lithium enhances TRAIL-induced apoptosis in human lung carcinoma A549 cells - Yan Lan; Xiufeng Liu; Rong Zhang; Kai Wang; Yao Wang; Zi-Chun Hua (BioMetals, 2013)

Flexible change and cooperation between mitochondrial electron transport and cytosolic glycolysis as the basis for chilling tolerance in tomato plants - Kai Shi; Li-Jun Fu; Shuai Zhang; Xin Li; Yang-Wen-Ke Liao; Xiao-Jian Xia; Yan-Hong Zhou; Rong-Qing Wang; Zhi-Xiang Chen; Jing-Quan Yu (Planta, 2013)

Magma mingling and chemical diffusion in the Taojiang granitoids in the Hunan Province, China: evidences from petrography, geochronology and geochemistry - Kai-Xing Wang; Pei-Rong Chen; Wei-Feng Chen; Hong-Fei Ling; Kui-Dong Zhao; Zhi-Qiang Yu (Mineralogy and Petrology, 2012)

Molecular cloning and functional characterization of a novel apple MdCIPK6L gene reveals its involvement in multiple abiotic stress tolerance in transgenic plants - Rong-Kai Wang; Ling-Li Li; Zhong-Hui Cao; Qiang Zhao; Ming Li; Ling-Yun Zhang; Yu-Jin Hao (Plant Molecular Biology, 2012)

Occupational risks and lung cancer burden for Chinese men: a population-based case–referent study - Lap Ah Tse; Ignatius Tak-sun Yu; Hong Qiu; Joseph Siu Kai Au; Xiao-rong Wang (Cancer Causes & Control, 2012)

Inhibition of Endogenous Hydrogen Sulfide Generation is Associated with Homocysteine-Induced Neurotoxicity: Role of ERK1/2 Activation - Xiao-Qing Tang; Xin-Tian Shen; Yi-E Huang; Rong-Qian Chen; Yan-Kai Ren; Heng-Rong Fang; Yuan-Yuan Zhuang; Chun-Yan Wang (Journal of Molecular Neuroscience, 2011)

Increased urinary 8-hydroxy-2′-deoxyguanosine levels in workers exposed to di-(2-ethylhexyl) phthalate in a waste plastic recycling site in China - Qian Wang; Li Wang; Xi Chen; Kai Min Rao; Shao You Lu; Sheng Tao Ma; Pu Jiang; Dan Zheng; Shun Qing Xu; Hong Yan Zheng; Jian Shu Wang; Zhi Qiang Yu; et al. (Environmental Science and Pollution Research, 2011)

Combination of Hyaluronic Acid Hydrogel Scaffold and PLGA Microspheres for Supporting Survival of Neural Stem Cells - Ying Wang; Yue Teng Wei; Zhao Hui Zu; Rong Kai Ju; Mu Yao Guo; Xiu Mei Wang; Qun Yuan Xu; Fu Zhai Cui (Pharmaceutical Research, 2011)

Enhanced yield performance of Bt rice under target-insect attacks: implications for field insect management - Hui Xia; Bao-Rong Lu; Kai Xu; Wei Wang; Xiao Yang; Chao Yang; Ju Luo; Fengxiang Lai; Wenli Ye; Qiang Fu (Transgenic Research, 2011)

Establishment of a transgene expression system for the marine microalga Schizochytrium by 18S rDNA-targeted homologous recombination - Ru-Bin Cheng; Xiang-Zhi Lin; Zhao-Kai Wang; Shan-Jun Yang; Hui Rong; Yong Ma (World Journal of Microbiology and Biotechnology, 2011)

PTEN status is related to cell proliferation and self-renewal independent of CD133 phenotype in the glioma-initiating cells - Ru-Bin Cheng; Rui-Juan Ma; Zhao-Kai Wang; Shan-Jun Yang; Xiang-Zhi Lin; Hui Rong; Yong Ma (Molecular and Cellular Biochemistry, 2011)

Ovate family protein 1 as a plant Ku70 interacting protein involving in DNA double-strand break repair - Yung-Kai Wang; Wen-Chi Chang; Pei-Feng Liu; Mu-Kai Hsiao; Chueh-Tsun Lin; Shih-Ming Lin; Rong-Long Pan (Plant Molecular Biology, 2010)

Ophiocerol, a novel macrocylic neolignan from the aquatic fungus Ophioceras dolichostomum YMF1.00988 - Jin-Yan Dong†; Le Wang†; Hong-Chuang Song; Li-Mei Wang; Kai-Ze Shen; Rong Sun; Guo-Hong Li; Lei Li; Ke-Qin Zhang (Natural Product Research, 2010)

Differential expression of TRPC channels in the left ventricle of spontaneously hypertensive rats - Fang-fang Liu; Zhi-yong Ma; Duo-ling Li; Jin-bo Feng; Kai Zhang; Rong Wang; Wei Zhang; Li Li; Yun Zhang (Molecular Biology Reports, 2010)

The Avoidance Responses of Daphnia magna to the Exposure of Organophosphorus Pesticides in an On-Line Biomonitoring System - Zong-Ming Ren; Zhi-Liang Li; Jin-Miao Zha; Kai-feng Rao; Mei Ma; Zijian Wang; Rong-Shu Fu (Environmental Modeling & Assessment, 2009)

Cloning and characterization of phosphorus starvation inducible Brassica napus PURPLE ACID PHOSPHATASE 12 gene family, and imprinting of a recently evolved MITE-minisatellite twin structure - Kun Lu; You-Rong Chai; Kai Zhang; Rui Wang; Li Chen; Bo Lei; Jun Lu; Xin-Fu Xu; Jia-Na Li (Theoretical and Applied Genetics, 2008)

Molecular Cloning and Expression of IL2 cDNA from the Tibet Pig - Li Hui; Gao Rong; Wu Mei; Wang Li-Huan; Fu Man-Liang; Wu Kai-Yuan (Veterinary Research Communications, 2005)